Gut microbiota in a host-brood parasite system: insights from common cuckoos raised by two warbler species - Schmiedová, Lucie; Kreisinger, Jakub; Požgayová, Milica; Honza, Marcel; Martin, Jean-François; Procházka, Petr (FEMS microbiology ecology, 2020)
An animal's gut microbiota (GM) is shaped by a range of environmental factors affecting the bacterial sources invading the host. At the same time, animal hosts are equipped with intrinsic mechanisms enabling regulation of GM. However, there is limited knowledge on the relative importance of these forces. To assess the significance of host-intrinsic vs environmental factors, we studied GM in nestlings of an obligate brood parasite, the common cuckoo (Cuculus canorus), raised by two foster species, great reed warblers (Acrocephalus arundinaceus) and Eurasian reed warblers (A. scirpaceus), and compared these with GM of the fosterers' own nestlings. We show that fecal GM varied between cuckoo and warbler nestlings when accounting for the effect of foster/parent species, highlighting the importance of host-intrinsic regulatory mechanisms. In addition to feces, cuckoos also expel a deterrent secretion, which provides protection against olfactory predators. We observed an increased abundance of bacterial genera capable of producing repulsive volatile molecules in the deterrent secretion. Consequently, our results support the hypothesis that microbiota play a role in this antipredator mechanism. Interestingly, fosterer/parent identity affected only cuckoo deterrent secretion and warbler feces microbiota, but not that of cuckoo feces, suggesting a strong selection of bacterial strains in the GM by cuckoo nestlings.
Keywords: Parasites; Animals; zpěvní ptáci; Passeriformes; mikrobiota; paraziti; zvířata; Microbiota; Songbirds; střevní mikroflóra; Gastrointestinal Microbiome